EKSPERIMENTASI MODEL PEMBELAJARAN THINK PAIR SHARE DENGAN PENDEKATAN KONTEKSTUAL PADA MATERI LOGARITMA DITINJAU DARI KECERDASAN MATEMATIS LOGIS SISWA KELAS X PADA SEKOLAH MENENGAH ATAS DI KABUPATEN CILACAP TAHUN PELAJARAN 2012/2013 - Biyarti, Tunggu; Riyadi, Riyadi; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2013)
Abstract : The purpose of this research were to know: (1) which of learning model gave a better learning mathematics result, learning model Think Pair Share (TPS), Think Pair Share with contextual approachment (TPSPK) or direct learning; (2) for each level of student’s logical mathematical intellegence, which of learning model gave a better learning mathematics result, learning model TPS, TPSPK or direct learning (PL). This research was quasi experimental research with 3 x 3 factorial design. The population in this research was senior high school students grade X in Cilacap. Sample was taken using stratified cluster random sampling technique. Study sample were the students of SMA Negeri 1 Binangun, SMA Negeri 1 Kroya and SMA Negeri Adipala. Instruments used to gather data were logical mathematical intellegence test and mathematics learning result test on the subject of logarithm. Both instruments were tested first before they were used. The test method included content validity, power, difficulty level and reliability. Testing of hypothesis used unbalanced two-ways analysis of variance using significance level of. Before doing the hypothesis test, the pre-condition test for variance analysis was done. The pre-condition test included population normality test using Lillieforce method and population variance homogeneity test using Bartlett method. Balance test toward mathematics initial ability data using unbalanced one-way analysis of variance. Based on hypothesis test, the conclusion were as follows: (1) learning models of TPS and TPSPK gave equally good results in learning mathematics, but learning model of TPS gave learning mathematics result better than direct learning one, while learning models of TPSPK and direct learning one gave equally good results in learning mathematics; (2) for each level of student’s logical mathematical intellegence, the three learning models, TPS, TPSPK and direct learning one gave equally good results in learning mathematics.Keyword: TPS, Contextual Approachment, Logical Mathematical Intellegence, Learning Mathematics Result.